2004
DOI: 10.1126/science.1099414
|View full text |Cite
|
Sign up to set email alerts
|

Jun Turnover Is Controlled Through JNK-Dependent Phosphorylation of the E3 Ligase Itch

Abstract: The turnover of Jun proteins, like that of other transcription factors, is regulated through ubiquitin-dependent proteolysis. Usually, such processes are regulated by extracellular stimuli through phosphorylation of the target protein, which allows recognition by F box-containing E3 ubiquitin ligases. In the case of c-Jun and JunB, we found that extracellular stimuli also modulate protein turnover by regulating the activity of an E3 ligase by means of its phosphorylation. Activation of the Jun amino-terminal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
423
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(448 citation statements)
references
References 24 publications
19
423
2
1
Order By: Relevance
“…87 The E3 ligase Itch can not only catalyze ubiquitination and degradation of PLCg and Bcl10, but also causes depletion of the AP-1 family members JunB and c-Jun upon TCR/CD28 engagement. 88 Thus, Itch can interfere at multiple levels with lymphocyte activation, which is in agreement with the profound immunological disorders that are caused through ablation of Itch in mice. 89,90 In this respect, it is interesting to note that Itch activity can be modulated by JNK, which indicates a novel function of JNK as a negative regulator of T cell signalling.…”
Section: Cd28 Sets the Threshold: The Role Of Ubiquitin Ligasessupporting
confidence: 52%
See 1 more Smart Citation
“…87 The E3 ligase Itch can not only catalyze ubiquitination and degradation of PLCg and Bcl10, but also causes depletion of the AP-1 family members JunB and c-Jun upon TCR/CD28 engagement. 88 Thus, Itch can interfere at multiple levels with lymphocyte activation, which is in agreement with the profound immunological disorders that are caused through ablation of Itch in mice. 89,90 In this respect, it is interesting to note that Itch activity can be modulated by JNK, which indicates a novel function of JNK as a negative regulator of T cell signalling.…”
Section: Cd28 Sets the Threshold: The Role Of Ubiquitin Ligasessupporting
confidence: 52%
“…89,90 In this respect, it is interesting to note that Itch activity can be modulated by JNK, which indicates a novel function of JNK as a negative regulator of T cell signalling. 88 Not only do CD28-derived signals impinge on the expression and activity of ubiquitin E3 ligases, but also ICOSmediated signalling is repressed by the RING-type ubiquitin ligase Roquin. 91 Sanroque (san/san) mice, which carry a homozygous mutation in the roquin gene, develop an autoimmune phenotype that resembles human systemic erythematosus and display a substantial increase in previously activated memory T cells.…”
Section: Cd28 Sets the Threshold: The Role Of Ubiquitin Ligasesmentioning
confidence: 99%
“…Recent studies provide insight into the mechanisms of c-Jun and JunB turnover. 13,14 Interestingly, Gao et al 14 demonstrated that JunB (and c-Jun) abundance can be regulated by extracellular stimuli in T-cells through Jun-N terminal kinase (JNK)-dependent phosphorylation of the novel E3 ligase Itch.…”
Section: Discussionmentioning
confidence: 99%
“…One ligase is the human COP1, which forms a multi-subunit ubiquitin ligase complex, DCX hDET1ÀhCOP1 and promotes c-Jun degradation regardless of c-Jun's phosphorylation status (Wertz et al, 2004). A second ligase is Itch, whose E3 ligase activity needs to be activated by JNKs through phosphorylation, causing the degradation of c-Jun in a manner independent of c-Jun phosphorylation by JNKs (Gao et al, 2004). The third c-Jun E3 ligase is Fbw7 (also called Fbxw7, CDC4, AGO and SEL10; Nateri et al, 2004), which forms a ligase complex with SKP1 and CUL1 that is referred to as SCF FBW7 (Welcker and Clurman, 2008).…”
Section: Introductionmentioning
confidence: 99%